Tubulocystic Carcinoma of the Kidney: A Case Report of Natural History and Long-Term Follow-Up - Kelvin A. Moses; John J. DeCaro; Adeboye O. Osunkoya; Muta M. Issa (The Scientific World Journal)
Tubulocystic carcinoma (TC) is a rare primary renal tumor that has been recently described in the pathology literature. Formerly termed low-grade collecting duct carcinoma, further molecular analysis has shown TC to be a distinct entity that is separate from the more aggressive collecting duct carcinoma. Previous series have described the microscopic and immunohistochemical features of this tumor. We describe the natural history of this tumor in a patient who was followed with active surveillance for several years and then underwent partial nephrectomy. Long-term follow-up has shown no evidence of disease. A review of the pertinent literature is performed.